Generation of competitor DNA fragments for quantitative PCR. - Uberla, K; Platzer, C; Diamantstein, T; Blankenstein, T (Genome Research, 1991)
A convenient and generally applicable method for the generation of competitor DNA fragments for quantitative PCR is described. Using mouse-specific primers, fragments are amplified from DNA of an evolutionarily distantly related species under low-stringency annealing conditions. Because these artificially created fragments contain the mouse primer specific ends, they can be used for the quantification of the mouse DNA amplified by these primers. Competitor DNA fragments that differ in size from the corresponding mouse DNA are selected to distinguish both fragments visually by gel electrophoresis. Competitor DNA fragments were generated for mouse beta-actin, interleukin-1, and tumor necrosis factor (TNF). Co-amplification of beta-actin cDNA for adjustment of equal amounts of input cDNA and subsequently TNF cDNA from lipopolysaccharide (LPS)-activated and nonactivated spleen cells with serial dilutions of the respective competitor DNA fragments allowed a semiquantitative comparison of the ratio of TNF mRNA present in both cDNA samples. Under certain conditions, the competitor DNA fragments can be used to determine the approximate molar concentration of a mRNA.